A New Biological System For Detecting Environmetal Carcinogens And /Or Mutagenes And Their Adversary - Mohammed, B. M.A; Katy, N.Sh (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A  new  test  system  for  detecting  environment  carcinogenes and/or  mutagenes  and  their  adversary  It  has  been  induced.  One hundred and fifty   mutants   were isolated from   the basidiomycete fungus Coprinus cinereus   which were   resistant to guanine analogue S- az.aguanine .All the spontaneous and induced with UV light origin mutants were isolated from the wild type strains Bc9/6.6 and  Hd5.5.These mutants were te ted on selective medium containing  differentconcentrations of the analogue and also to their ability to usc purine bases and their degredated  products as  a sole  nitrogene source were tested ; and their ability to grow on HAT   medium was tested . According  to  the results obtained  from these test;  mutants  wereclassified into four phenotypic groups for each  iJd -type strain .All  the  8-az.aguanine  resistant  mutants  were  d.ikaryotized   withcompatible wild strains. The dikaryons produced were unable to grow on  medium           containing        8-az.aguanine                     which               establish the recessiveness of the mutations to their respective wi ld-type alleles. Complementation   test  detcrmind  four  genes   which  controll   the resi stance  to 8- azaguaninc in Coprinus cincres   .These genes were desi gnated  azg-1, azg-2, azg'-3, azg-4.Three of these genes azg-1, azg-2 and azg'-4werc carried by Bc9/6.6 and Hl /5.5 mutants. While, azg-3 gene  was found in Bc9/6.6 mutants only.These  genes  are determ.ind for  the  first  time  in  fungus coprinus cinereus  .Mutants which carry azg-1  gene were characterized by their inability to use   hypozanthine and                                              guanine as a sole nitrogen source in themedium ; their failure to grow  on HAT medium  and their resistanceto all concentrations of 8- az.aguanine used.This gene is considered to    IBN AL- HAITHAM J.FOH PURE & API'L.SCI.         VOL.19(4) 2006 represent  a mutation led to   lose or   modify the specificity of the enzyme hypoxauthine -guanine phosphoribosyl transferase (HGPRT) whi ch play an important role in transferring hypoxauthine and guanine to their nucleotides  by salvage pathway.Spore analysis indi cated that azg'-1  gene locted in linkage group II,since it gave a distance of 28 map units with the mating type geneB.The assessment of the cytotoxic , mutagn ic and antimutagcâ€¢tic role ofthe  aqueous extract of  garl ic     (Allium  sativum  L.)  against the genotoxic effect of mitomycin - C( MMC ) evaluate the ability of the mutagen to induce mutation inHGPRT gene by    using the asexual spores (oidia )of Copninus cineraus for the strain AZG78 and by depending on the viabil ity and mutation rate in HGPRT gene test .To assess cytotoxity and mutagenecity of garlic extract , gradual concentrations were prepared . The concentration of choice was considered with respect to  two factors ; high survi val rate and low mutagenic  activity (similar to negative control ). To examine the antimutagenic  effects of  the extract, an interation was made between the crude  extract and the mutagen   MMC with respect to three kinds of treatments before , aOer and with mutagen . The study concentrated on two sides 1- on the toxic and /or m utagenic effect of the aqueous extract of garlic . 2 - Antimutagenic activity of the extract with respect to   the mutageen MMC . However,   this activity was dependent on the type of the treatment . The extract showed best antimutagenic activity when it was used before the mutagen , so itis considered as desmutagen to the genotox i c effects of MMC.These data support the hypothesis that garlic compounds may be eflicacius in preventions of cancer and also we could use the HGPRTgene as  a  sensitive biological  system  in  detecting environmental mutagenes or carcinogens and their adversary .